Beekeeping in São Raimundo Nonato, Piauí, Brazil - Carvalho, Davina Maria de Castro; Amorim, Laerte Bezerra de; Souza, Darcet Costa; Costa, Carlos Pedro de Menezes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Belonging to the Integrated Territory of Serra da Capivara, semi-arid Brazil, the economy of São Raimundo Nonato is based on the agricultural sector with emphasis on honey production and small animal husbandry. The objective of the study was to perform an analysis of the environmental, social, economic and technical aspects of the beekeeping sector in the municipality of São Raimundo Nonato. A direct field survey was carried out with the application of a semistructured questionnaire, individually applied in the communities of São Vítor, Nova Jerusalém and Macacos. The average honey productivity in the year 2016 varied between 15 and 25 kg per hive/year and the total production was approximately 39,000 kg. The beekeeping activity in the communities collaborates expressively in the financial income of the families involved, strengthening the beekeeper/farmer and family is economy and permanence in the field, the net annual income of 80% of beekeepers is 5000 reais with the sale of honey. On the environmental aspect, there is an awareness of beekeepers in which the preservation of flora is substantial for the growth of the productive chain. Increasing productivity and exploiting new bee products such as propolis, royal jelly, pollen, wax and honeycomb in the pot are the biggest yearnings of beekeepers.